2011
DOI: 10.1093/humrep/deq387
|View full text |Cite
|
Sign up to set email alerts
|

Management of fertility preservation in prepubertal patients: 5 years’ experience at the Catholic University of Louvain

Abstract: BACKGROUND Since prepubertal boys cannot benefit from sperm banking, a potential alternative strategy for fertility preservation involves immature testicular tissue (ITT) banking aimed at preservation of spermatogonial stem cells. Survival of spermatogonia has been demonstrated after ITT freezing, which is considered ethically acceptable. We report the results of a pilot program set up for fertility preservation in prepubertal boys. METHODS All boys undergoing ITT cryobanking from May 2005 were identified from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 42 publications
0
84
0
3
Order By: Relevance
“…Therefore, fertility preservation should be included in the management of young males with cancer (Wyns et al, 2011). In pre-pubertal boys, no completely validated option is currently available for fertility preservation (Rives et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fertility preservation should be included in the management of young males with cancer (Wyns et al, 2011). In pre-pubertal boys, no completely validated option is currently available for fertility preservation (Rives et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In pre-pubertal boys, no completely validated option is currently available for fertility preservation (Rives et al, 2012). Freezing of testicular tissue or cell suspensions has been developed to cryopreserve pre-pubertal testes or SSCs respectively (Wyns et al, 2011). After thawing, SSCs must undergo a maturation process to restore the ability to produce spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of using SSCs to preserve and restore fertility in patients receiving gonadotoxic therapies has been extensively discussed (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In theory, testicular cells obtained via biopsy prior to cancer treatment could be cryopreserved and then retransplanted following clinical remission.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, testicular cells obtained via biopsy prior to cancer treatment could be cryopreserved and then retransplanted following clinical remission. Several clinics around the world, including our own Fertility Preservation Program in Pittsburgh (http://www.mwrif.org/220), are now performing testicular biopsies on boys prior to the initiation of cancer therapy in hopes that this tissue can be used in the future to restore fertility (8,9,30,31). However, to make SSC transplantation a realistic clinical option for the prepubertal patient cohort, two major hurdles must be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 14 prepubertal boys undergoing testicular biopsy demonstrated positive post-operative outcomes as well as insight into parental factors influencing a decision to undergo harvesting [17]. Furthermore, a study of 52 prepubertal patients (mean age: 6.43±3.32 years) and 10 peripubertal patients (mean age: 14±1.23 years) reported no significant complications [50]. While our study was different in reporting the bundling with other medical procedures, our overall safety findings of male patients were in accordance with other studies.…”
Section: Commentmentioning
confidence: 97%